Distinct immune cell dynamics correlate with the immunogenicity and reactogenicity of SARS-CoV-2 mRNA vaccine - Takano, Tomohiro; Morikawa, Miwa; Adachi, Yu; Kabasawa, Kiyomi; Sax, Nicolas; Moriyama, Saya; Sun, Lin; Isogawa, Masanori; Nishiyama, Ayae; Onodera, Taishi; Terahara, Kazutaka; Tonouchi, Keisuke; et al. (Cell reports. Medicine, 2022)
Two doses of Pfizer/BioNTech BNT162b2 mRNA vaccine elicit robust severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-neutralizing antibodies with frequent adverse events. Here, by applying a high-dimensional immune profiling on 92 vaccinees, we identify six vaccine-induced immune dynamics that correlate with the amounts of neutralizing antibodies, the severity of adverse events, or both. The early dynamics of natural killer (NK)/monocyte subsets (CD16+ NK cells, CD56high NK cells, and non-classical monocytes), dendritic cell (DC) subsets (DC3s and CD11c− Axl+ Siglec-6+ [AS]-DCs), and NKT-like cells are revealed as the distinct cell correlates for neutralizing-antibody titers, severity of adverse events, and both, respectively. The cell correlates for neutralizing antibodies or adverse events are consistently associated with elevation of interferon gamma (IFN-γ)-inducible chemokines, but the chemokine receptors CCR2 and CXCR3 are expressed in distinct manners between the two correlates: vaccine-induced expression on the neutralizing-antibody correlate and constitutive expression on the adverse-event correlate. The finding may guide vaccine strategies that balance immunogenicity and reactogenicity. [Display omitted] •Immune profiling of mRNA vaccinees reveals dramatic immunological changes•The dynamics of NK/monocyte subsets correlate with neutralizing-antibody response•The dynamics of dendritic cell subsets correlate with severity of adverse events•IFN-γ-inducible chemokines, but not the receptors, are related to these correlates Takano et al. identify cellular correlates for neutralizing-antibody titers and systemic adverse events following SARS-CoV-2 mRNA vaccination. The involvement of IFN-γ-mediated pathways is proposed. The findings give insights into balancing the immunogenicity and reactogenicity of mRNA vaccine.